Improving Housewives' Family Resilience during the Covid-19 Pandemic: Emotion Regulation Training Strategies - Anshori, Afif; Setiawan, Nugroho Arief; Junaidi, Junaidi (Universitas Islam Negeri Raden Intan Lampung, 2023)
The COVID-19 pandemic expanded rapidly to practically every country in a matter of months, and it can affect anybody, including the elderly, adults, young children, babies, pregnant women, and nursing moms. This study seeks to assess the effectiveness of emotion regulation training in increasing family resilience in housewives during the COVID-19 pandemic. The study employed a quantitative approach. It involved 50 housewives from the Muslimat NU Lampung Region as subjects determined by the purposive sampling technique. The researchers collected the data using the Family Resilience Assessment Scale (FRAS), which consists of 51 items compiled by Sixbey (2005). In addition, the researchers conducted a qualitative analysis by analyzing data collected through observations, interviews, and emotion regulation training. The data was analyzed using SPSS 24.0 for Windows. The results of this study show that t = -39.617 with Sig.0.000 (1% significance). Therefore, there was a significant difference in the family resilience of housewives before and after emotion regulation training. The findings revealed an increase in the value of family resilience before and after the study. Before the study, the average value of family resilience was 78.76, while after the study, it was 167.02. In this study, there were three categories of resilience percentage. The category of highly resilient housewives increased to 80%, the medium category dropped to 20%, and the low category fell to 0%. As a result, it is possible to conclude that the training effectively increased family resilience among housewives.